Skuteczność trabekuloplastyki pneumatycznej (PNT) u chorych z jaskrą otwartego kąta i nadciśnieniem ocznym – doniesienie wstępne - Wierzbowska, Joanna; Stankiewicz, Andrzej; Romańska, Łucja (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To evaluate the efficacy of PNT in lowering intraocular pressure (IOP) in patients treated for open angle glaucoma (OAG) and ocular hypertension (OH). Material and methods: The study group consisted of 24 eyes of 14 patients (10 F and 4 M), aged from 35 to 72 (mean 53.7 ± 8.7) who were treated for OAG or OH. Twelve patients were treated with prostaglandin analogues (PA) in monotherapy, one patient with PG and nonselective beta-bloker (BB) and one patient with PG, BB and topical carbonic anhydrase inhibitor (CAI). The baseline mean IOP measured with Goldmann tonometry one hour before first PNT procedure was 20.7 ± 3.3 mmHg (range 16-27). The PNT was performed routinely at 0 and 7-10 day using PNT Unit 1000-Coronado (Ophthalmic International, Inc., Fountain Hills, Arizona, USA). Then the IOP was measured monthly and if increased to the preoperative values the procedure was repeated. The mean observation time was 6 months, with the shortest and longest follow-up being 4 and 12 months, respectively. The IOP changes were estimated one hour after the first PNT on day 0, then on day 7-10, after 1, 2, 3, 4, 5 and 6 months. A paired Student`s t test was used for statistical analysis. Results: The mean IOP measured one hour after PNT was 19.26 ± 4.0 mmHg (p = 0.17). After 7 days mean IOP was 17.35 ± 2.64 mmHg (p<0.01), after one month 16.52 ± 2.81 mmHg (p<0.01) and after next months 16.37 ± 2.61 mmHg (p<0.01), 17.63 ± 2.28 mmHg (p<0.01), 15.64 ± 2.06 mmHg (p<0.01), 16.14 ± 3.42 mmHg (p< 0.01) i 16.64 ± 3.14 mmHg (p<0.01), respectively. The mean IOP reduction was 1.48 mmHg (7.14%) one hour after PNT procedure, 3.39 mmHg (16.35%) after 7-10 days, 4,22 mmHg (20.35%) after one month, then respectively 4.37 mmHg (21.07%), 3.11 mmHg (15.02%), 5.10 mmHg (24.59%), 4.60 mmHg (22.18%) i 4.10 mmHg (19.77%) after 2, 3, 4, 5 i 6 months of observation. In 8 eyes the procedure was repeated again after 3 months, in 4 eyes after 6 months and in 2 eyes after 12 months. After the procedures transient moderate conjunctival hyperemia was observed in 24 eyes (100%) and mild subconjunctival hemorrhagies in 4 eyes (16%). Lasting a few hours after the PNT procedure foreign body sensations occured in 3/14 patients (21%). Conclusions: PNT is an effective method of lowering IOP in patients treated for OAG and OH.